1981
DOI: 10.1111/j.1096-3642.1981.tb01593.x
|View full text |Cite
|
Sign up to set email alerts
|

The middle ear of the skull of birds: the ostrich, Struthio camelus L.

Abstract: The morphology of the middle ear region including the basicranium and quadrate ofSfncchio is very siiidiii. io tlir saiiic region in the orders Procellariiformes. Pelecaniformes. Ciconiiformes and Sphenixifomies. Strufhio though, has some unique middle ear characters such as the lack ofa chorda tympani nerve, the arrangement of the glossopharyngeal and vagus nerve foramina, the structure in the upper neck of the external ophthalmic vein and the position of the Eustachian tube. The articulatory surfaces for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The images are modified from Tahara and Larsson (2019) extension into the surrounding bones at a later developmental stage, a process called (secondary) pneumatization given that pneumatization of bones are often evident as smooth walled recesses, fossae, or foramina. These external pneumatic morphologies have been studied in a wide range of birds (e.g., Norberg, 1978;Saiff, 1974Saiff, , 1976Saiff, , 1978Saiff, , 1981Saiff, , 1982Saiff, , 1988Saiff, , 2006Saiff, , 2011Starck, 1995;Vorster & Starck, 2003).…”
mentioning
confidence: 99%
“…The images are modified from Tahara and Larsson (2019) extension into the surrounding bones at a later developmental stage, a process called (secondary) pneumatization given that pneumatization of bones are often evident as smooth walled recesses, fossae, or foramina. These external pneumatic morphologies have been studied in a wide range of birds (e.g., Norberg, 1978;Saiff, 1974Saiff, , 1976Saiff, , 1978Saiff, , 1981Saiff, , 1982Saiff, , 1988Saiff, , 2006Saiff, , 2011Starck, 1995;Vorster & Starck, 2003).…”
mentioning
confidence: 99%
“…Macke (1969) focused on the development of the skull of the coot (Fulica atra) and gave only minor attention to the middle ear structures. Saiff (1981Saiff ( -1988 and most recently J.M. Starck (1995) presented specialized investigations in the paleognathous middle ear.…”
mentioning
confidence: 99%
“…Nervus vagus and n. glossopharyngeus “are very closely related both topographically and functionally” (Akester, , p. 398), and in palaeognathous birds both nerves exit through a single foramen (Bourdon & Lindow, ; Elzanowski, ; Müller, ; Saiff, ). In most Neognathae, by contrast, there is a separate foramen for nervus glossopharyngeus, which is usually situated at the medial margin of the fossa parabasalis (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Although detailed studies of the course of the cranial nerves were published for some galloanserines (Akester, 1979;Gheţie, 1976, fig. 325), Psittaciformes (Manogue & Nottebohm, 1982;Wild, 1981), Passeriformes (Conrad, 1915;Nottebohm & Nottebohm, 1976), as well as some Podicipediformes and Rallidae (Conrad, 1915), descriptions of the basicranial nerve foramina are sparse and scattered in the literature (e.g., Elzanowski & Galton, 1991;Saiff, 1974Saiff, , 1978Saiff, , 1981Saiff, , 1988Weber, 1990). Most previous authors described 2-3 foramina nervi hypoglossi (FNH) for neornithine birds, but as shown in the present study, there exists more variability in the number, size, and arrangement of these foramina than what is apparent from the literature.…”
mentioning
confidence: 99%